2018
DOI: 10.1136/bmjopen-2017-019829
|View full text |Cite
|
Sign up to set email alerts
|

Association of prehypertension and hyperhomocysteinemia with subclinical atherosclerosis in asymptomatic Chinese: a cross-sectional study

Abstract: ObjectivesComorbid hypertension and hyperhomocysteinemia is an important risk factor for carotid atherosclerotic plaque formation. We put forward the hypothesis that the subjects with comorbid prehypertension and hyperhomocysteinemia also had an increased risk of subclinical atherosclerosis, using carotid intima–media thickness (CIMT) as the marker of the atherosclerotic process.MethodsA total of 4102 asymptomatic Chinese subjects aged 18–60 years were divided into four groups according to blood pressure (BP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Bianca et al [ 33 ] suggested that HCY exerted a prothrombotic effect by enhancing platelet aggregation. Several studies also showed that HHCY might enhance the adverse effects of CAD risk factors such as essential hypertension, smoking, dyslipidemia, and diabetes mellitus [ 34 37 ]. These were probably related to the formation and progression of CAD in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Bianca et al [ 33 ] suggested that HCY exerted a prothrombotic effect by enhancing platelet aggregation. Several studies also showed that HHCY might enhance the adverse effects of CAD risk factors such as essential hypertension, smoking, dyslipidemia, and diabetes mellitus [ 34 37 ]. These were probably related to the formation and progression of CAD in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…A direct association between plasma Hcy levels and CAD has been found in observational epidemiological studies [ 12 ]. Homocysteine could produce complex changes within the blood vessel wall [ 30 ] and may cause CAD through the following 5 pathways [ 31 33 ]: (a) vascular endothelial cell damage and dysfunction; (b) dyslipidemia; (c) promotion of the expression of inflammatory factors (e.g., the expression of tumor necrosis factor- α and inducible nitric oxide (NO) synthase (iNOS)); (d) impaired endothelium-mediated platelet inhibition, which enhances coagulation function and induces thrombosis; and (e) stimulation of vascular smooth muscle cell proliferation. Even mild or moderate elevation of plasma concentrations of Hcy (plasma Hcy > 16 µM) can affect coronary and peripheral arteries, eliciting vasomotor dysfunction and increased thrombosis, and consequently increased morbidity and mortality [ 10 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bianca et al [27] suggested that HCY exerted a prothrombotic effect by enhancing platelet aggregation. Also, several studies showed that HHCY might enhance the adverse effects of CAD risk factors such as essential hypertension, smoking, dyslipidemia, and diabetes mellitus [28][29][30][31]. These were probably related to the formation and progression of CAD in young adults.…”
Section: Discussionmentioning
confidence: 99%